Scanning probe microscopy of functional materials nanoscale imaging and spectroscopy - Kalinin, Sergei V.; SpringerLink (Online service). (New York Springer, 2010)
Novel scanning probe microscopy (SPM) techniques are used for the characterization of local materials functionalities ranging from chemical reactivity and composition to mechanical, electromechanical, and transport behaviors. In this comprehensive overview, special emphasis is placed on emerging applications of spectroscopic imaging and multifrequency SPM methods, thermomechanical characterization, ion-conductance microscopy, as well as combined SPM-mass spectrometry, SPM-patch clamp, and SPM-focused X-ray applications. By bringing together critical reviews by leading researchers on the application of SPM to the nanoscale characterization of functional materials properties, Scanning Probe Microscopy of Functional Materials provides insight into fundamental and technological advances and future trends in key areas of nanoscience and nanotechnology. Key Features: ?Serves the rapidly developing field of nanoscale characterization of functional materials properties ?Covers electrical, electromechanical, magnetic, and chemical properties of diverse materials including complex oxides, biopolymers, and semiconductors ?Focuses on recently emerging areas such as nanoscale chemical reactions, electromechanics, spin effects, and molecular vibrations ?Combines theoretical aspects with applications ranging from fundamental physical studies to device characterization.
I. Emergent phenomena in strongly-correlated systems: Phase separation and novel quaziparticles in nanowires -- STM of ruthenates and manganites -- STM of superconductors -- STM of cuprates -- II. Semiconductor and photovoltaic materials: SPM of solar materials -- Cross-sectional STM of semiconductor heterostructures -- Charge dynamics in photovoltaic polymers -- III. Functional probing of biosystems and macromolecules: Molecular Imaging of biomembranes single molecules with electrically functionalized probes -- AFM/patch clamp in biology -- Electrical imaging of membranes -- Cell dynamics by Ion conductance microscopy -- Ferroelectric polymers -- IV. SPM of magnetic materials: Spin manipulation by STM -- Magnetic Resonant Force Microscopy -- Magnetic Force Microscopy -- V. Electromechanics on the nanoscale: ferroelectrics and multiferroics: New dynamic modes and energy dissipation in SPM -- Polarization dynamics in relaxor ferroelectrics -- Piezoresponse Force Spectroscopy -- Polarization dynamics in capacitors and heterostructures -- VI. Mechanical properties: Nanomechanics by SPM -- Atomic Force Acoustic Microscopy of functional materials -- VII. Optical methods: NSOM and NSOM-transport -- NSOM -- Optical machines and unfolding -- Optically-assisted pump-probe STM -- VIII. Emerging SPM applications: STM/NC-AFM -- Scanning Non-linear Dielectric Microscopy -- Vibrational spectroscopy of single molecule -- Ultrafast ac STM -- SPM and electron microscopy combined -- In-situ STEM-nanoindentation -- Material characterization by SPM-focused X-ray combination -- *see Long ToC for tentative contributors.
2011 in website.
Electronic reproduction.
Keywords: Scanning probe microscopy; Electronic books